Karakteristik Pasien Gagal Jantung Akut di Instalasi Gawat Darurat RSUP. Prof. Dr. R. D. Kandou Manado - Simbage, Jeanet Sofiola; Malara, Reginus; Mulyadi (Mapalus Nursing Science Journal, 2024)
Background: Acute heart failure is a life-threatening disease that requires appropriate care. The emergency department (ED) plays an important role in the long-term care of patients with acute heart failure. The mortality rate of acute heart failure patients is very high, and visits to the emergency room are expected to continue to increase every year. Objective: This study aimed to determine the demographic, clinical and diagnostic characteristics of acute heart failure patients. Method: This study used descriptive research by taking secondary data with a research sample of 107 obtained through a purposive sampling technique. Results: This study found that the highest distribution of patients in the age group> 60 years (48.5%) and dominant male patients (71%) with no history of smoking (74.8%) and alcohol consumption (82.2%). Most of the patients' main complaints were shortness of breath (42.1%) with normal pulse examination (64.5%), normal respiration examination (76.6%) normal systolic blood pressure examination (55.1%) and normal diastolic blood pressure examination (58.9%). Ejection fraction examination results <40% echocardiography (71%) and cardiomegaly thorax photo examination results (47.7%). Conclusion: There are variations in the characteristics of patients with acute heart failure in the emergency room of the hospital. Prof. DR. R. D. Kandou Manado. This study can inform health workers about the characteristics of patients with heart failure.